School Information Management in Using Social Media (Whatsapp, Instagram, Youtube and Facebook) - Mochamad Mansur, Yoma; Hidayati, Dian (Mudir : Jurnal Manajemen Pendidikan, 2023)
The rapid advancement of technology has made a shift in perspective in interacting, communicating and obtaining information, including by thinking more practically about utilizing social media. Including in the world of education, social media should be the leading tool in conveying information, communication, and as a learning medium and even as a school branding tool. Therefore, school leaders must build managerial information systems, especially in the use of social media so that the delivery of information, communication, learning and school image runs effectively and efficiently. The method used in this study is a descriptive qualitative approach. The results of the study show that managerial use of social media involves several teachers who have potential and competence in the field of technology. The team is part of the Mutu Creative Center (MCC) working group (Pokja) under the coordination line of the vice principal appointed by the Principal. Based on the functions and benefits in the theory of the 7 honeycombs of social media, 4 social media are selected which are currently very familiar to use and fulfill these functions, namely WhatsApp, Instagram, YouTube and Facebook by displaying various features and functions. Those social media are the most frequently used by technology users in Indonesia